Ekstrak Sambiloto Menurunkan Patogenesitas Ookista Eimeria Tenella - Yellita, Yulia; Cahyaningsih, Umi; Pradono, Dyah Iswantini; Winarsih, Wiwin; Manalu, Wasmen (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
Eimeria tenella is one of the nine of Eimeria species, a pathogenic intraseluler protozoa causing aviancoccidiosis. Infection was initiated by the ingestion of sporulated oocysts. The aim of this study was toinvestigate the effect of E. tenella oocyst incubation in methanol extract of Andrographis paniculata beforeinfection in broiler performance. This research used 115 broiler DOC (CP 707) devided into five groups,each group consisted of 23 broilers. The infection with 1x105 oocyst were done at the 14th day old of chicken.The 1st group was placebo (KN), while the 2nd group was infected with unincubated oocyst (KP), and theother three groups i.e. : 3rd, 4th, 5th were infected with incubated oocyst in A. paniculata extract for 2, 4, and6 hours, respectively. The number of oocysts in feces were counted on day 5th to 14th post-infection, theheterophile and macrophages were counted from caecum histology preparation, by slaughtered threechickens of each of groups on the day 0,3,6.9, and 14 post infection, and accretion body weight wasmeasured by weighing chickens per week to five-week old chickens. The results of this study indicated thatthe incubation period the sporulated oocyst in the extract of A.paniculata for six hours before infection,reduced the number of oocysts production in the feces, the number of inflammatory cells (macrophages andheterophile) in the cecum, and increases body weight (gain). In conclusion A.paniculata extract decreasedthe pathogenisity of E.tenella oocyst, so the extract of A.paniculata has good potential as anticoccidia. Itis high likely that A. paniculata extract has a potential to be anticoccidia.
Keywords: Incubated oocyst Eimeria tenella, Andrographis paniculata methanol extract, broiler